The role of burial markers in the socio-religious life of a People-Shona and Israelite socities in focus. - Mwandayi, Canisius (2016)
One of the most vivid memories from my childhood experiences is the day I unknowingly sat on a mould of soil and played with a pillar of stone that had been placed at the edge of the mould. What had drawn my attention to the stone was that it looked simply unique from other stones that w ere around. On being told, however, that it was a tomb where my grandmother had been buried years hack. I felt a shiver go up the spine for i knew from one of the family teachings that it w as a taboo sitting and playing on a grave. The prohibition went further even to bar children from going tradition/teaching found its way into the pen of Bourdillon (1976) who writes that graves are avoided because o f the fear of death as well as fear of the occult powers which are believed to linger around graves. He goes further to mention that a case of madness, for example, in a small boy could be attributed to his stumbling across a grave while herding cattle and other similar mishaps could also be a result of proximity of graves (Bourdillon.1976). Echoing similar sentiments is Julie Ruggi 2000) who argues that cemeteries are for the most part considered sacred in so far as the site is 'regarded with respect.' Much of this respect, as she further argues, rests largely on the fuel that the site acts as a context for grief, and it is the bereaved that need to be protected from inappropriate activity Rugg, 2000). It is such teachings among the Shona in particular that made me sweat upon realization that I had been playing with a grave. While my grandmother had since passed on. (lie burial markers on her grave stood as a testimony that she had been interred on that spot and they stood also as a point o f contact between her dead spirit and her living family members. Grave markers too were a reminder for the living to keep off from disturbing those who were 'resting.' What was done to my deceased grandmother was not unique toner alone Hut this has since time immemorial been the practice across various cultures. It is due to the quest to understand more the meaning and significance of these burial markers that this chapter makes a comparative analysis between Shona and Israelite burial customs since they share a lot in common. Before embarking, however, on the main task or the work I shall briefly look at the issue of interment in both cultures since it often determines the kind of burial markers to be placed on graves.